The Influence of Promotion and Service Quality on the Competitive Advantage of Mobile Haircut Services - Fitri Aulina (Yayasan Kita Menulis, 2026)
This research addresses the demanding mobile service business model by examining how Promotional strategies and Service Quality standards impact Competitive Advantage. The study adopted a quantitative survey approach, gathering information from Mobile Haircut Service customers located in Bintang Bayu District. Analysis via Multiple Linear Regression indicated that Promotion and Service Quality jointly exhibit a positive and significant impact on the dependent variable. Crucially, the partial results highlight that Service Quality holds the largest influence. This suggests that to secure long-term competitiveness, mobile haircut service companies must prioritize the consistent enhancement of service quality and integrate it effectively with robust promotional activities that reach and retain customers.